Contextual factors related to physical activity during daily middle school physical education. Issue 9 (September 2016) - Brusseau, Timothy A.; Burns, Ryan D.; Fu, You
Abstract: Objectives: Given the importance of optimizing physical activity in adolescents, the purpose of this study was to examine the effect of activity mode, environment, and semester on step counts/minute and MVPA during daily middle-school physical education (PE). Design: A prospective and observational research design. Methods: Participants included 232 students (Mean age = 13.3 ± 0.4 years) recruited from the seventh and eighth grades from one public middle-school in the U.S. Activity modes were employed across the school year including motor skills, games, and fitness activities located in indoor and outdoor environments. Step counts/minute and MVPA were monitored across 132 PE lessons during Fall and Spring semesters using NL-1000 piezoelectric pedometers. A three-way Multivariate Analysis of Covariance (MANCOVA) was employed to examine the effect of activity mode (skill games vs. fitness), environment (indoors vs. outdoors), and semester (Fall vs. Spring) on student step counts/minute and MVPA. MANCOVA was followed by separate ANCOVA tests. Results: MANCOVA yielded a statistically significant three-way interaction (Wilks' Λ  = 0.98 F (2, 1153) = 8.9, P  < 0.001). Follow-up tests supported that physical activity was higher during outdoor fitness activities in the Fall compared to indoor motor skills in the Spring for step counts/minute (Mean difference = 27.0 steps/minute, P  < 0.001, Cohen's d  = 1.6) and MVPA (Mean difference = 7.8 min, P  < 0.001, Cohen's d  = 2.0). Conclusions: Daily middle-school physical activity was the highest during outdoor fitness activities in the Fall and the lowest during indoor motor skill games in the Spring.